2022
DOI: 10.1111/php.13688
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Ultrafast Photoinitiated Dynamics of the Hachimoji 5‐aza‐7‐deazaguanine Nucleobase: Impact of Synthetically Expanding the Genetic Alphabet

Abstract: The guanine derivative, 5‐aza‐7‐deazaguanine (5N7CG) has recently been proposed as one of four unnatural bases, termed Hachimoji (8‐letter) to expand the genetic code. We apply steady‐state and time‐resolved spectroscopy to investigate its electronic relaxation mechanism and probe the effect of atom substitution on the relaxation mechanism in polar protic and polar aprotic solvents. Mapping of the excited state potential energy surfaces is performed, from which the critical points are optimized by using the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
2
0
1
Order By: Relevance
“…Moreover, only singlet states were involved in both studies, while the triplet states that might play important roles during the deactivation of UBPs upon excitation were totally neglected. Very recently, Krul et al 52 explored the ultrafast photophysics of UNB P consisting P-Z pair employing the combination of time-resolved spectroscopy and high level XMS-CASPT2 calculations. They found that the excitation to the lowest energy 1 ππ* state of P results in complex dynamics leading to ca.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only singlet states were involved in both studies, while the triplet states that might play important roles during the deactivation of UBPs upon excitation were totally neglected. Very recently, Krul et al 52 explored the ultrafast photophysics of UNB P consisting P-Z pair employing the combination of time-resolved spectroscopy and high level XMS-CASPT2 calculations. They found that the excitation to the lowest energy 1 ππ* state of P results in complex dynamics leading to ca.…”
Section: Introductionmentioning
confidence: 99%
“…As described in detail in the Supporting Information, the transient absorption data were corrected for the hydrated electron signal that originates from the two-photon absorption of the water solvent using the method developed by Kohler and co-workers . Importantly, we also collected transient data exciting at 267 nm with low photon density conditions to avoid the formation of hydrated electrons from the solvent, as previously described. The latter results are shown in Figures S2–S6. The transient absorption signals under both conditions are very similar from ca.…”
mentioning
confidence: 99%
“…Para maiores detalhes recomendamos a leitura do nosso artigo "Resolving Ultrafast Photoinitiated Dynamics of the Hachimoji 5-aza-7-deazaguanine Nucleobase: Impact of Synthetically Expanding the Genetic Alphabet" publicado na edição especial de 50 anos do jornal "Photochemistry and Photobiology". 158 O Resumo do nosso artigo é reproduzido a seguir.…”
Section: Modificação Química Seletiva: 5-aza-7-deazaunclassified